Pelanggaran Tata Tertib yang dilakukan oleh Siswa Di sekolah dan Implikasinya terhadap Pelayanan Bimbingan dan Konseling - Hendri, Yulfi; Daharnis, Daharnis; Nurfahanah, Nurfahanah (Konselor, 2014)
One of the school's efforts is to help students achieve good learning results by instill discipline in the students. The fact that there are still students who commit breaches of the school rules, even though the school has undertaken the construction of discipline by the school personnel. This research aims to describe a breach of the school rules undertaken by students and the cause factors. Type of this research is descriptive research. The population in this research is 308 students and samples is 174 students. The research results reveal the overall student violations committed at the school belongs to medium category. Based on the level of violations committed students at the school were categorized in medium, and high in learning time. The cause factors violations committed student who comes from a family environment factors is in high category, from the school environment are medium category, and from the community is in high category.